PENINGKATAN KEMAMPUAN BERBICARA DENGAN MENGGUNAKAN METODE VAKT (VISUAL,AUDITORI,KINESTETIK,TAKTIL) ANAKÂ TUNARUNGUÂ KELASÂ I PADA SEKOLAH LUAR BIASA - UDJIJANTI, EMY (Jurnal Pendidikan Khusus, 2017)
ABSTRACT: Problem of deaf children is obstacles in language development because language is an important tool to communicate with others. In order to be able to develop oral communication skill, these children need to be taught how to speak using VAKT (visual, auditory, kinesthetic, tactile). This method uses visual (vision sense), auditory (audio sense), kinesthetic (doing activity), and tactile (touch sense). This method is good and right in teaching  how to speak to the deaf children. The VAKT method can be used to the children with disorders of language,  phonic consciousness, vocabulary development, reading and writing. This research aims to analyze the improvement of  speaking skill by using the VAKT method to the deaf children in class of D1 at SLB (extra ordinary school) of Al Farah Menganti Gresik. This is a class action research  (PTK) with Kemmis and Mc Taggart design meaning this research uses cycle class action research. Subject of this research is three deaf children  at SLB of Al Falah Menganti Gresik. Data was collected by using  observation and test techniques. Then data  was analyzed by using descriptive quantitative technique  presented in forms of table and bar graphic. Data in numeral form then was descripted thereby producing meaning and can be concluded.  Results of the research indicate that activity of teacher in cycle I and II is  62.5 and 77.8 respectively; activity of children in cycle I and II is 66.7 and 81.2 respectively; and score of result of speaking in the same cycle is 64.6 and 79.2 respectively. From this results, it can be concluded that there is improvement of speaking skill by using VAKT method to the deaf children of class I at SLB of Al FalahMenganti Gresik.   Keywords: speaking ability, VAKT method